Kinetic Analysis in Horses With Deep Digital Flexor Tendinopathy Within the Digit Diagnosed by Magnetic Resonance Imaging - Madsen, Lori M.; Gutierrez-Nibeyro, Santiago D.; Stewart, Matthew C.; McCoy, Annette M.; Schaeffer, David J. (Frontiers in Veterinary Science, 2022)
Objectives: To determine the stance duration and ground reaction forces (GRF) of horses with deep digital flexor (DDF) tendinopathy at the level of the foot and compare the stance duration and GRF to those of clinically sound horses. Design: Prospective clinical study. Animals: Sixteen horses (Seven horses with bilateral forelimb lameness, four horses with unilateral forelimb lameness, and five horses with no lameness). Procedures: Analyses of kinetic variables were performed on both forelimbs from sound horses and horses diagnosed with chronic DDF tendinopathy. Stance duration and longitudinal and vertical components of the GRF were determined for the limbs of clinically sound horses and limbs of horses with DDF tendinopathy. Separate Spearman correlation analyses were used to assess potential association within groups (combined left and right forelimbs of clinically sound horses, lamest limbs of horses with DDF tendinopathy, and contralateral limbs of horses with DDF tendinopathy) and with the set of kinetic variables. Analysis of variance on mean ranks of tied values was used to determine differences in kinetic variables between groups (PROC GLIMMIX) using the kinetic values of the clinically sound horses as the reference group. Results: There were a total of eleven lame horses. Seven horses had bilateral forelimb lameness and four had unilateral lameness. Of the eleven horses, there were fifteen DDF tendinopathies. There were eight dorsal border DDF tendinopathies, five core DDF tendinopathies, and two sagittal/parasagittal splits DDF tendinopathies. The most lame limbs of horses with DDF tendinopathy had significantly smaller values for peak vertical force and time of peak braking force than did forelimbs of clinically sound horses. Also, the most lame limbs of horses with DDF tendinopathy had significantly larger values for the time of peak vertical force than did forelimbs of clinically sound horses. Conclusions and clinical relevance: Horses with chronic DDF tendinopathies develop certain alterations of GRF parameters. This information can be used in future studies to determine if particular kinetic variable changes in horses with DDF tendinopathies differ from those of horses with other pathologies within the foot and therefore could be diagnostic.